1977
DOI: 10.1080/15287397709529584
|View full text |Cite
|
Sign up to set email alerts
|

Effects in rats and guinea pigs of short‐term exposures to sulfuric acid mist, ozone, and their combination

Abstract: Ozone and the oxides of sulfur are common environmental pollutants. The acute pulmonary lesions caused by ozone and sulfuric acid mist in rats and guinea pigs have been characterized. Rats are not affected by sulfuric acid mist in concentrations up to 100 mg/m3 except for reduced body weight at the higher doses. A true alveolitis develops in guinea pigs exposed to more than 20 mg/m3 sulfuric acid mist. The ozone lesion is primarily confined to the terminal bronchioles and proximal alveoli. In combination studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Less is known about the effects of sulfates on the respiratory tract, but studies have shown that various forms are capable of inducing bronchial constriction and possibly a secondary alveolitis in guinea pigs (Amdur et al, 1978;Cavender et al, 1977a). Rats appear to be less susceptible than guinea pigs, and pulmonary function studies on humans, sheep, and dogs tend to show little or no effect of inhaled sulfate particles alone (Hackney et al, 1978;Sackner et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the effects of sulfates on the respiratory tract, but studies have shown that various forms are capable of inducing bronchial constriction and possibly a secondary alveolitis in guinea pigs (Amdur et al, 1978;Cavender et al, 1977a). Rats appear to be less susceptible than guinea pigs, and pulmonary function studies on humans, sheep, and dogs tend to show little or no effect of inhaled sulfate particles alone (Hackney et al, 1978;Sackner et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, we examined the e ects on pulmonary surfactant activity of exposure to high concentrations of acid in two species, the guinea pig and the rat. The two species were chosen for their di erent responsiveness to acid aerosols as assessed by pulmonary physiology, morphology, and changes in bronchoalveolar lavage ( BAL) uid [19][20][21] . Surface tension properties were measured using a captive bubble surfactometer ( CBS) [ 22] .…”
mentioning
confidence: 99%
“…Controlled clinical and laboratory studies have demonstrated that H 2 SO 4 , a potent irritant to both the upper airways and deep lung (Amdur et al, 1986;Folinsbee, 1989), can (1) alter airway responsiveness in rabbits (Gearhart & Schlesinger, 1986;El-Fawal & Schlesinger, 1994); (2) decrease pulmonary function, particularly in young asthmatic children (Koenig et al, 1989); (3) reduce mucociliary clearance in mid-sized and small airways in healthy nonsmoking adults (Leikauf et al, 1984); (4) cause cell damage leading to alveolitis, bronchiolar epithelial desquamation, and edema in rats and guinea pigs (Cavender et al, 1977); and (5) produce a persistent hypertrophy and hyperplasia of epithelial secretory cells in the tracheobronchial tree of rabbits (Gearhart & Schlesinger, 1989). The pulmonary defense system is one of many potential targets of inhaled air pollutants.…”
mentioning
confidence: 99%